2012
DOI: 10.5812/asjsm.34519
|View full text |Cite
|
Sign up to set email alerts
|

Static Stretching of the Hamstring Muscle for Injury Prevention in Football Codes: a Systematic Review

Abstract: Purpose: Hamstring injuries are common among football players. There is still disagreement regarding prevention. The aim of this review is to determine whether static stretching reduces hamstring injuries in football codes.Methods: A systematic literature search was conducted on the online databases PubMed, PEDro, Cochrane, Web of Science, Bisp and Clinical Trial register. Study results were presented descriptively and the quality of the studies assessed were based on Cochrane's 'risk of bias' tool. Results:Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Thigh injuries are similarly thought to be caused by decreased flexibility and muscle weakness of the thighs. It has been reported that static stretching and improvement in flexibility are effective in preventing thigh injuries 25‐27 . The intervention in this study improved the HBD and SLR angle, which we consider as related to the reduced incidence of thigh injuries.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Thigh injuries are similarly thought to be caused by decreased flexibility and muscle weakness of the thighs. It has been reported that static stretching and improvement in flexibility are effective in preventing thigh injuries 25‐27 . The intervention in this study improved the HBD and SLR angle, which we consider as related to the reduced incidence of thigh injuries.…”
Section: Discussionmentioning
confidence: 60%
“…The study intervention improved the flexibility of the lower limbs, leading to a reduction in the overall injury rate. It has been previously reported that decreased flexibility and muscle weakness can cause injuries, and stretching and improvement in flexibility are effective for injury prevention 23‐29 . Lumbar/lower back injuries are thought to be caused by decreased flexibility around the hip joint and muscle weakness of the trunk muscles.…”
Section: Discussionmentioning
confidence: 99%
“…This situation means that evaluative clinical processes must constantly be fine-tuned, along with the application of specific tests (Brukner et al, 2014). On the other hand, Rogan, Wust, Schwitter and Schmidtbleicher (2013) promote the need to systematically perform flexibility evaluations as one of the alternatives to prevent injuries in sport.…”
Section: Introductionmentioning
confidence: 99%
“…muscles showing the greater tendency to shorten [2,4]. The hamstring are the group of muscles that have a tendency to shorten even among young, healthy individuals and in recreational athletes [5].…”
mentioning
confidence: 99%